Considerable impacts of AGXT2 V140I polymorphism on chronic heart failure in the Chinese population. (August 2016) - Hu, Xiao-Lei; Zhou, Ji-Peng; Kuang, Da-Bin; Qi, Hong; Peng, Li-Ming; Yang, Tian-Lun; Li, Xi; Zhang, Wei; Zhou, Hong-Hao; Chen, Xiao-Ping
Abstract: Background and aims: Alanine-glyoxylate aminotransferase 2 (AGXT2) polymorphisms have been extensively studied to be associated with many cardiovascular diseases, with the exception of chronic heart failure (CHF). The aim of this study was to determine whether the AGXT2 rs37369 (V140I) polymorphism is associated with risk for and prognosis of CHF in Chinese patients. Methods: 1000 CHF patients and 1200 healthy controls were recruited and polymerase chain reaction-restriction fragment length polymorphism analysis (PCR-RFLP) was used to determine the genotypes of rs37369 polymorphism. Tube formation assay and transwell migration assay were performed to assess the effects of asymmetric dimethylarginine (ADMA) and to explore the significance of rs37369 polymorphism in the pathogenesis of CHF. 140 CHF patients underwent a median follow-up of 38.7 months by telephone. Results: The rs37369 GG genotype was significantly over-represented in CHF patients compared to controls (18.9% vs 14.7%, p  = 0.009) and was significantly associated with increased risk of CHF ( p  = 0.030), especially in patients with hypertension ( p  = 0.021). Besides, the rs37369 GG genotype marginally increased the risk for CHF in smokers. ADMA stimulated migration and inhibited tube formation of cultured human umbilical vein endothelial cells (HUVECs). Overexpression of AGXT2 with pcAGXT2-rs37369-A or G plasmid reversed ADMA-induced HUVECs migration and tube formation. AGXT2 rs37369-A showed increased ADMA degradation activity and marginally prolonged the lifetime of CHF patients. Conclusions: ADMA might accelerate the progression of CHF possibly by inhibiting angiogenesis and promoting migration of HUVECs. AGXT2 rs37369 polymorphism is associated with increased risk for CHF, which may due to distinct disparities of alleles in ADMA degradation. Highlights: AGXT2 rs37369 polymorphism is significantly associated with increased risk for CHF. AGXT2 rs37369 polymorphism influences activity of AGXT2 in ADMA degradation. ADMA can stimulate migration and inhibit the tube formation of HUVECs. ADMA may aggravate CHF via inhibiting angiogenesis and promoting migration.